Development of Wunderlich syndrome following a Russell's viper bite. (August 2022) - Senthilkumaran, Subramanian; Miller, Stephen W.; Williams, Harry F.; Savania, Ravi; Thirumalaikolundusubramanian, Ponniah; Patel, Ketan; Vaiyapuri, Sakthivel
Abstract: Snakebite envenomation is a high priority neglected tropical disease that predominantly affects rural communities living in developing countries. Due to myriad of complications including coagulopathies, neurotoxicity, nephrotoxicity and local tissue destruction, treating snakebite victims is a major challenge for clinicians. Russell's viper ( Daboia russelii ) is one of the 'Big Four' venomous snakes in India, and it is responsible for the most snakebite-induced deaths and disabilities. Acute kidney injury occurs frequently following Russell's viper bites and it is a critical factor contributing to disabilities, deaths and excessive treatment costs. In addition to commonly observed envenomation effects, Russell's viper bites induce some rare complications such as priapism, sialolithiasis and splenic rupture. Here, we report a case of Wunderlich syndrome that developed in a 22-year-old male following a Russell's viper bite. The patient displayed severe coagulopathies, abdominal tenderness, and hypotension. Notably, a peri-nephric haematoma was identified through ultrasound and computerised tomographic imaging. The haemorrhage was successfully treated using angioembolisation, and the patient recovered without any difficulties. Although a clinical condition such as this is rare, it is important to create awareness among treating clinicians about its occurrence, diagnosis and clinical management. Graphical abstract: Image 1 Highlights: Snakebite-induced Wunderlich syndrome is a rare clinical event. We report Russell's viper bite-induced Wunderlich syndrome (WS) in a young healthy victim. The patient displayed peri-nephric haematoma around the right kidney along with coagulopathy, abdominal pain and hypotension typical for WS. This condition was treated using angioembolisation. Clinicians should be aware of WS and its symptoms when treating snakebite victims.